Generation of gene corrected human isogenic iPSC lines (IDVi003-A_CR13, IDVi003-A_CR21, IDVi003-A_CR24) from an inherited retinal dystrophy patient-derived IPSC line ITM2B-5286-3 (IDVi003-A) carrying the ITM2B c.782A > C variant using CRISPR/Cas9 - Ben yacoub, Tasnim; Letellier, Camille; Wohlschelegel, Juliette; Condroyer, Christel; Slembrouck-Brec, Amélie; Goureau, Olivier; Zeitz, Christina; Audo, Isabelle (Stem cell research, 2023)
The ITM2B-related retinal dystrophy (ITM2B-RD) was identified within patients carrying the autosomal dominant variant [c.782A > C, p.(Glu261Ala)] in ITM2B from whom induced pluripotent stem cell (IPSC) lines were previously generated. Here, we report the generation of three isogenic control iPSC lines from the derived affected subject cell line (ITM2B-5286-3) using CRISPR/Cas9 engineering. The three generated lines express pluripotency markers, can be differentiated into the three germ layers and present a normal karyotype. The generated iPSC lines can be used to study the implications of ITM2B-RD variant in vitro.